2015
DOI: 10.5966/sctm.2014-0208
|View full text |Cite
|
Sign up to set email alerts
|

The Lymph Node as a New Site for Kidney Organogenesis

Abstract: The shortage of organs for kidney transplantation has created the need to develop new strategies to restore renal structure and function. Given our recent finding that the lymph node (LN) can serve as an in vivo factory to generate or sustain complex structures like liver, pancreas, and thymus, we investigated whether it could also support kidney organogenesis from mouse renal embryonic tissue (metanephroi). Here we provide the first evidence that metanephroi acquired a mature phenotype upon injection into LN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Our studies indicate that the lymph node can serve as an in vivo factory to generate complex organ structures, including liver, pancreas, thymus, and kidney (6064). This in vivo bioreactor might offer unprecedented opportunities to study stem cell maturation and function, as well as provide a unique organogenesis site for therapeutic purposes.…”
Section: The Lymph Node Bioreactormentioning
confidence: 90%
“…Our studies indicate that the lymph node can serve as an in vivo factory to generate complex organ structures, including liver, pancreas, thymus, and kidney (6064). This in vivo bioreactor might offer unprecedented opportunities to study stem cell maturation and function, as well as provide a unique organogenesis site for therapeutic purposes.…”
Section: The Lymph Node Bioreactormentioning
confidence: 90%
“…Oxidative stress and apoptosis were markedly reduced as well. Francipane et al injected mouse embryonic kidneys into lymph nodes and found that they subsequently acquired mature phenotypes due to host cell stimuli [74]. They, too, observed urine-like fluid-containing cysts along with the appearance of filtration functions.…”
Section: Embryonic Whole Kidneys For Renal Regenerationmentioning
confidence: 97%
“…Our prior studies described the LN as an attractive bioreactor supporting the engraftment and function of adult mouse hepatic, pancreatic, and thymic cells (Komori, Boone, DeWard, Hoppo, & Lagasse, ) as well as the functional maturation of several mouse embryonic tissues, including the kidney (Francipane & Lagasse, , , ).…”
Section: Overviewmentioning
confidence: 99%